In memoriam: Moisés Béhar (1922-2015) - Ossenbach, Carlos (2015)
Moi, as he liked to be called by family and friends, passed away on February 14th in Jerusalem, where he had enjoyed the last years of his life in the loving care of his daughter Jacqueline. At the age of 92, he now rests in peace in the Mount of Olives Cemetery. After Otto Mittelstaedt (1919-2000) and Otto Tinschert (1915-2006), Guatemala’s orchidology has now lost the third of its founding fathers.